MODEL PEMEKARAN WILAYAH YANG MENYEJAHTERAKAN MASYARAKAT - Tijan, - (Forum Ilmu Sosial, 2009)
Expansion of area is intended to overcome the problem of administrative, political, economic, social,Ã‚Â cultural, and defense security faced by the autonomous regions as a result of environmental changes.Ã‚Â However, in reality in Indonesia, not least Expansion of area actually cause new problems. Many ofÃ‚Â the new autonomous regions are not able to fnance themselves, boundary dispute, local citizen confictÃ‚Â with new citizen because they do not agree combined with Ã¢â‚¬Å“other communityÃ¢â‚¬Â, and seizure of naturalÃ‚Â resources. Normative reference in the form of Law No. 32/2004 on Regional Governance and RegulationÃ‚Â No. 129 of 2000 on Expansion Area, during this itÃ¢â‚¬â„¢s read by the local elite as an opportunity to expandÃ‚Â their region not as a responsibility to realize what is a noble goal of expansion area. Opportunities areÃ‚Â interpreted by the elites as an opportunity to gain some benefts, such as the existence of new positionsÃ‚Â in the executive and legislative environment. Therefore, necessary to formulate a model of area by usingÃ‚Â democratic procedures, which open opportunities formation of a new area based on local demand, soÃ‚Â participate, going from the bottom, and welfare of the people.Keywords : Area expansion, welfare of the people